Market Power, Resource Extraction and Pollution: Some Paradoxes and a Unified View - Luca Lambertini; George Leitmann (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
We adopt a stepwise approach to the analysis of a dynamic oligopoly game in which production makes use of a natural resource and pollutes the environment, starting with simple models where firms' output is not a function of the natural resource to end up with a full-fledged model in which (i) the resource is explicitly considered as an input of production and (ii) the natural resource and pollution interact via the respective state equations. This allows us to show that the relationship between the welfare properties of the economic system and the intensity of competition is sensitive to the degree of accuracy with which the model is constructed.
Keywords: C73; H23; L13; O31; Q2; Q3; 330